Pengaruh Stimulasi Media Gambar Kartun Indonesia Terhadap Karakter Building Kedisiplinan Memilah Sampah Pada Anak Usia Dini Usia 4-6 Tahun Di PAUD Kecamatan Gamping Kabupaten Sleman - Yustiana Olfah; Ni Ketut Mendri; Bambang Suwerda (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2017)
Discipline attitude in maintaining the environment cleanliness, especially in sorting garbage should be introduced at an early age1. The essence of early education is to provide some stimulation in order to optimize all children potential (body / physical or spiritual / mental), including the sorting of garbage that has not been optimally done in early childhood. There are many kinds of stimulation techniques for character education in early childhood, through sound, music, movement, touch, talking, singing, reading, matching, comparing, classifying, solving problems, scribbling, drawing, and stringing. The aim of this experiment is to determine the effect of stimulation of the picture media on character building discipline on sorting garbage at an early age children (4-6 years old) at Playgroup in Gamping, Sleman, Yogyakarta. The type of this research is Quasi Research with "Pre test Post test with Control Group Design". The research sample was taken by random sampling. The observation of control Grup was done twice. The first observation was to see the behavior of garbage sorting discipline before being given the stimulation and the second observation done after stimulation. Sampling was done by purposive sampling with criteria of children aged 4-6 years. Data examination results were analyzed descriptively and analytically with SPSS for windows version 16.0 using T-Test and Kendal Tau significance level of 0.05. The results showed that before treatment the mean value of garbage sorting discipline was 84.23, and the mean value after treatment was 95.88. The mean difference between the value of post and pre treatment groups was 11.65. Before being given stimulation using media poster, mean value of the discipline of garbage sorting was 84.3, and the mean value after treatment was 84.76. The conclusion of the study is the stimulation of Indonesian cartoons media has a significant effect (p = 0.000) on character building garbage sorting at an early age children aged of 4-6 years in Play Group in Gamping, Sleman, Yogyakarta. There is no significant relationship (p = 0.070, viewed from the frequency value at the level of discipline of the group post, the majority of respondents are at high level of discipline, and no distribution of scores on all categories (high, medium, low). It is recommended for teachers of early childhood education in Gamping, Sleman, Yogyakarta utilize Indonesian cartoons media to improve discipline in sorting garbage for children, their students, and for the next researcher to conduct advanced research on the use of Indonesian cartoon media rather than media cartoon abroad which has been a favorite of children in building character to sort garbage in early childhood / kindergarten.